The Benefits and Costs of Volunteering in Community Organizations: Review and Practical Implications - Matthew J. Chinman and Abraham Wandersman (Nonprofit and Voluntary Sector Quarterly 28(1) 1999, 1999)
The authors reviewed the literature of the benefits and costs associated with articipation in voluntary organizations. The literature shows that benefits and costs can be measured, are related to participation, and can be managed by voluntary organization leaders. Therefore, understanding benefits and costs is important because they can be used to enhance participation in voluntary groups. Membership, activity level, and different organization types are ways in which researchers have examined benefits and costs. Researchers have also collapsed benefit and cost items into factors and constructed a direct ratio of benefits to costs. Practical implications of the research are discussed, and recommendations are given to refine future research efforts.